A tribo Lavoisiereae (Melastomataceae) no Parque Nacional da Serra da Canastra, Minas Gerais, Brasil - Alves, Rodolfo Ferreira (2022)
The current study catologed 26 species of the Lavoisiereae tribe in the Serra da Canastra National Park (SCNP), Minas Gerais, Brazil. Microlicia, with 24 species, is the most representative genus, followed by Rhynchanthera, with two species. An identification key for the species, morphological descriptions, taxonomic comments, geographical distribution, habitat, flowering, and fruiting data are provided. Also, Microlicia sp. 1 and Microlicia sp. 2, endemic to SCNP, are described here and compared with similar morphologically species.